The National Library of Finland - strengthening the Finnish Library System - Ekholm, Kai (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
On Thursday 29 June 2006, the President of the Republic approved the amendment of the Universities Act which changes the Finnish name of the Helsinki University Library, Helsingin yliopiston kirjasto, to Kansalliskirjasto, the National Library of Finland. The Library will remain an independent institute within the University of Helsinki. The amended Universities Act enters into force on 1 August 2006.